A Test of the Modigliani‐Miller Invariance Theorem and Arbitrage in Experimental Asset Markets - CHARNESS, GARY; NEUGEBAUER, TIBOR (Journal of Finance, 2019)
ABSTRACT Modigliani and Miller show that the total market value of a firm is unaffected by a repackaging of asset return streams to equity and debt if pricing is arbitrage‐free. We investigate this invariance theorem in experimental asset markets, finding value‐invariance for assets of identical risks when returns are perfectly correlated. However, exploiting price discrepancies has risk when returns have the same expected value but are uncorrelated, in which case the law of one price is violated. Discrepancies shrink in consecutive markets, but persist even with experienced traders. In markets where overall trader acuity is high, assets trade closer to parity.